Usability of the GrabMerchant Application: An Evaluation using the System Usability Scale and the Retrospective Think Aloud Method - Handayani, Rima; Maria, Evi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
GrabMerchant is an application used by GrabFood and GrabMart business partners to manage various business operations, including order processing, inventory management, and promotional activities. Despite its widespread use, user satisfaction remains relatively low, with an average rating of 3.8 out of 5 based on 214,000 reviews—lower than its competitor, GoBiz, which has a rating of 4.1 out of 5 from 195,000 reviews. Several issues reported by users—such as errors in the notification feature, inventory management, and promotion setup—indicate potential usability problems. This study aims to evaluate the usability level of the GrabMerchant application using the System Usability Scale (SUS) and the Retrospective Think Aloud (RTA) method. The SUS method is used to measure users’ perceptions of the application's ease of use, while the RTA method helps assess effectiveness and efficiency, as well as identify issues that may not be detected through quantitative measurements. The findings show that GrabMerchant received a SUS score of 74.01, which places its usability in the “Good” category based on the adjective rating scale. The application’s effectiveness rate was recorded at 93%, indicating high success in task completion, while efficiency was measured at 0.35 goals per second, suggesting that task completion time could still be improved. Furthermore, the study identified several key issues, including difficulty locating features, an unappealing interface design, and a lack of user guidance. Based on these findings, the study proposes several recommendations, such as adding a search feature, optimizing the user interface—e.g., by clarifying icon layouts, minimizing redundancy, improving contrast, and using more distinct color variations for feature icons—as well as providing simulators and in-app tutorials. Implementing these recommendations is expected to improve the overall usability of the GrabMerchant application, enhance the user experience, and ultimately increase user loyalty.